H19 Promotes HCC Bone Metastasis Through Reducing Osteoprotegerin Expression in a Protein Phosphatase 1 Catalytic Subunit Alpha/p38 Mitogen‐Activated Protein Kinase–Dependent Manner and Sponging microRNA 200b‐3p. Issue 1 (9th May 2021) - Huang, Zhao; Chu, Liang; Liang, Junnan; Tan, Xiaolong; Wang, Yu; Wen, Jingyuan; Chen, Jin; Wu, Yu; Liu, Sha; Liao, Jingyu; Hou, Rui; Ding, Zeyang; et al.
Abstract : Background and Aims: Bone is the second most frequent site of metastasis for HCC, which leads to an extremely poor prognosis. HCC bone metastasis is typically osteolytic, involving the activation of osteoclasts. Long noncoding RNA H19 plays an important role in the pathogenesis of human cancers. Nonetheless, the mechanism underlying the participation of H19 in HCC bone metastasis remains unclear. Approach and Results: The current study established a mouse HCC bone metastasis model by using serial intracardiac injection and cell isolation to obtain cells with distinct bone metastasis ability. H19 was highly expressed in these cells and in clinical HCC bone metastasis specimens. Both osteoclastogenesis in vitro and HCC bone metastasis in vivo were promoted by H19 overexpression, whereas these processes were suppressed by H19 knockdown. H19 overexpression attenuated p38 phosphorylation and further down‐regulated the expression of osteoprotegerin (OPG), also known as osteoclastogenesis inhibitory factor. However, up‐regulated OPG expression as well as suppressed osteoclastogenesis caused by H19 knockdown were recovered by p38 interference, indicating that p38 mitogen‐activated protein kinase (MAPK)–OPG contributed to H19‐promoted HCC bone metastasis. Furthermore, we demonstrated that H19 inhibited the expression of OPG by binding with protein phosphatase 1 catalytic subunit alpha (PPP1CA), which dephosphorylates p38. SB‐203580‐mediated inactivation of p38MAPK reversed the down‐regulation of HCC bone metastasis caused by H19 knockdown in vivo . Additionally, H19 enhanced cell migration and invasion by up‐regulating zinc finger E‐box binding homeobox 1 through the sequestration of microRNA (miR) 200b‐3p. Conclusions: H19 plays a critical role in HCC bone metastasis by reducing OPG expression, which is mediated by the PPP1CA‐induced inactivation of the p38MAPK pathway; and H19 also functions as a sponge for miR‐200b‐3p.